Method for solid-state storage of graphene oxide and application thereof
By mixing and drying an aqueous graphene oxide solution with an anionic surfactant or anionic polyelectrolyte, a soluble graphene oxide solid is prepared, which solves the aggregation problem of graphene oxide powder during storage and achieves efficient solid-state storage and high single-piece rate. The preparation of dispersions improves the performance and application potential of the material.
Patent Information
- Application Number
- CN202411467159.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to suppress irreversible aggregation during storage of existing graphene oxide powders, resulting in a decrease in performance during solid storage, and the high monolithic rate of the dispersion is difficult to guarantee.
Soluble graphene oxide solid (SGS) is prepared by mixing an aqueous graphene oxide solution with an anionic surfactant or anionic polyelectrolyte and drying it. This method is simple and stable, and can completely restore the monolithic state.
The efficient and solid storage of graphene is realized, and it can be completely dispersed in the water. The prepared graphene membrane has the mechanical properties that are similar to the membrane that are directly prepared with decentralized liquid, which improves production efficiency and application potential.
Smart Images

Figure CN119330349A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for storing graphene oxide, in particular to a method for storing graphene oxide in a solid state and application thereof. Background Art
[0002] Graphene oxide (GO) is a highly anticipated two-dimensional material and a precursor for high-performance graphene-based assembly materials. Due to its excellent mechanical, electrical and thermal properties, graphene-based assembly materials have gradually emerged in the fields of aerospace, military industry and energy storage, and are gradually moving towards large-scale applications. For the preparation of high-performance graphene-based assembly materials, it is very important to use a precursor GO with uniform size, high single-piece rate and appropriate functional group content. At present, the industry generally uses GO water or N,N-dimethylformamide (DMF) dispersion as the raw material for preparing assemblies. GO dispersed in water or DMF can maintain stable properties and molecular structure for a long time. In addition, dispersant molecules can effectively prevent the irreversible agglomeration of GO, so that it can maintain a high single-piece rate. However, the mass concentration of GO dispersion is often below 5 wt.%, and the content of effective substances is very low, which brings great trouble to the storage and transportation of GO raw materials.
[0003] Patent CN101993065A "A method for preparing graphene powder" and patent CN106966383A "A paper ball-shaped graphene microsphere and its preparation method" proposed the idea of processing GO into powder for solid-state storage. However, it is difficult to suppress the irreversible aggregation between GO during the preparation process with existing methods, which also makes it difficult for these powders to be completely and evenly dispersed in solvents such as water or DMF, let alone ensure a high monolithic rate of the dispersion. In this way, the performance of the assembly material prepared using GO powder dispersion is difficult to reach a similar level as that prepared using GO dispersion. How to completely restore GO solid to a monolithic state is the key to achieving GO solid-state storage. Summary of the invention
[0004] In view of the problems existing in the prior art, a method for storing graphene oxide in the solid state and its application are proposed. This method overcomes the defects of the existing storage of graphene oxide powder and prepares a completely soluble graphene oxide solid. The soluble graphene oxide solid prepared in this way not only has the advantages of high solid-state storage bulk density and convenient transportation, but also can be completely dispersed into a single piece in water. From a technical point of view, compared with the existing graphene oxide powder production process, this method has a simple preparation process, stable process and higher production efficiency. In addition, the soluble graphene oxide solid can be quickly dispersed in water, DMF and other dispersants to form a stable single-piece graphene oxide dispersion. The use of soluble graphene oxide solid as a raw material for preparing graphene-based assemblies does not increase the production cycle too much, thereby affecting the overall production efficiency. The graphene oxide film prepared using the soluble graphene oxide solid has mechanical properties similar to those of the film directly prepared using the graphene oxide dispersion, showing the extremely high application potential of this method.
[0005] To this end, the present invention provides the following technical solution: a method for storing graphene oxide in a solid state, comprising adding an anionic surfactant or an anionic polyelectrolyte to an aqueous solution of graphene oxide and mixing the mixture evenly, and then drying the mixed solution to prepare a soluble graphene oxide solid (SGS).
[0006] Furthermore, the concentration of the graphene oxide aqueous solution is 1-20 mg / g.
[0007] Furthermore, the anionic surfactant is one of sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (SDBS), sodium stearate, sodium oleate, and sodium hexadecyl sulfate.
[0008] Furthermore, the anionic polyelectrolyte is one of sodium polystyrene sulfonate (PSS), sodium alginate (SA), sodium lauryl ether sulfate (SLES), sodium polyacrylate, and polyvinyl ammonium phosphate.
[0009] Furthermore, the mass ratio of graphene oxide aqueous solution to ionic surfactant or anionic polyelectrolyte is 10:3~1:1. If it exceeds 1:1, the ionic surfactant or anionic polyelectrolyte in the mixture will become the main component and will not play the role of storing GO.
[0010] Furthermore, the drying temperature of the drying treatment is 20°C to 40°C, and the drying time is three hours to one day.
[0011] The beneficial effects of this application are: The dispersion of GO is mixed with anionic surfactants or anionic polyelectrolytes, and SGS can be obtained after simple drying. This method is simple to operate and suitable for scale-up. By utilizing the characteristics that anionic surfactants and anionic polyelectrolytes can be adsorbed on the sp2 region of GO sheets, GO sheets are isolated from each other, thereby blocking the π-π stacking between sheets and inhibiting the tendency of agglomeration. The prepared SGS can be completely restored to a single sheet state without agglomerated insoluble matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a physical picture of the SGS prepared in Example 1 of the present invention; Figure 2 is the X-ray diffraction (XRD) pattern of the SGS prepared by the present invention; Figure 3 This is a physical picture of the SGS prepared in Example 1 of the present invention being dissolved in water and then left to stand overnight; Figure 4 is the OM diagram of the SGS prepared by the present invention after being dissolved in water, wherein: Figure 4 a is the OM image of SGS prepared in Example 1, Figure 4 b is the OM image of SGS prepared in Example 2, Figure 4 c is the OM image of SGS prepared in Example 3, Figure 4 d is the OM image of SGS prepared in Example 4, Figure 4 e is the OM image of SGS prepared in Example 5, Figure 4 f is the OM image of SGS prepared in Example 6, Figure 4 g is the OM image of SGS prepared in Example 7, Figure 4 h is the OM image of SGS prepared in Example 8, Figure 4 i is the OM image of SGS prepared in Example 9; Figure 5 is a SEM picture of the SGS prepared by the present invention after being dissolved in water, wherein: Figure 5 a is the SEM image of SGS prepared in Example 1, Figure 5 b is the SEM image of SGS prepared in Example 2, Figure 5 c is the SEM image of SGS prepared in Example 3, Figure 5 d is the SEM image of SGS prepared in Example 4, Figure 5 e is the SEM image of SGS prepared in Example 5, Figure 5 f is the SEM image of SGS prepared in Example 6, Figure 5 g is the SEM image of SGS prepared in Example 7, Figure 5 h is the SEM image of SGS prepared in Example 8, Figure 5i is the SEM image of SGS prepared in Example 9; Figure 6 The left figure is an AFM photograph of SGS prepared in Example 1 of the present invention after being dissolved in water, and the right figure is a corresponding track height map; Figure 7 This is a physical picture of the regenerated GO membrane prepared from the SGS dispersion prepared in Example 1 of the present invention; Figure 8 is a comparison chart of the tensile properties of the regenerated GO membrane prepared by the SGS dispersion prepared in Example 1 of the present invention and the ordinary GO membrane; Fig. 9 This is a real picture of the GO powder used in comparative example 1 after being dissolved in water and left to stand for 1 hour; Fig.10 is the OM diagram of the comparative sample prepared by the present invention after being dissolved in water, wherein: Fig.10 a is the OM image of GO powder used in Comparative Example 1, Fig.10 b is the OM image of SGS prepared in Comparative Example 2, Fig.10 c is the OM image of SGS prepared in Comparative Example 3; Fig.11 is a SEM image of the comparative sample prepared by the present invention after being dissolved in water, wherein: Fig.11 a is the SEM image of GO powder used in Comparative Example 1, Fig.11 b is the SEM image of SGS prepared in Comparative Example 2, Fig.11 c is the SEM image of SGS prepared in Comparative Example 3. DETAILED DESCRIPTION
[0013] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0014] The present invention mixes the dispersion of GO with anionic surfactant or anionic polyelectrolyte and then obtains SGS by simple drying. The method is simple to operate and suitable for scale-up. 2 The characteristics of the regions isolate the GO sheets from each other, thereby blocking the π-π stacking between the sheets and inhibiting the tendency of agglomeration. The prepared SGS can be completely restored to a single sheet state without agglomerated insoluble matter.
[0015] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0016] Example 1 A method for storing graphene oxide in a solid state, wherein SDBS is added to a 10 mg / g GO aqueous dispersion so that the mass ratio of GO to SDBS is 10:3, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0017] Take 10g of SGS and put it into 10g of water, stir until it is completely dispersed, and then concentrate it to 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, and perform OM, SEM, and AFM tests. Figure 4 a is the OM diagram, and it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 a is a SEM image, from which it can be seen that GO appears as a single piece in the dispersion; Figure 6 The left picture is the AFM picture. Figure 6 The right figure is the corresponding trajectory height map. It can be seen that the thickness of the final GO sheet is about 1 micron, which is consistent with the reports in the literature (Wang, Y.; Wang, S.; Li, P.; Rajendran, S.; Xu, Z.; Liu, S.; Guo, F.; He,Y.; Li, Z.; Xu, Z.; Gao, C. Conformational phase map of twodimensionalmacromolecular graphene oxide in solution. Matter 2020, 3, 230−245.). This shows that the obtained dispersion is uniform and GO exists in the form of a single sheet. The above dispersion is spread on the membrane and dried to obtain a regenerated GO membrane, such as Figure 7 The samples with a length of 10 mm and a width of 2 mm were prepared and subjected to tensile tests with a force of 50 N. The tensile properties were compared with those of commercial GO membranes (purchased from Gaoxin Technology) under the same conditions. Figure 8 , it can be seen that the tensile properties of the two are similar.
[0018] Example 2 A method for storing graphene oxide in a solid state, wherein SDBS is added to a 10 mg / g GO aqueous dispersion so that the mass ratio of GO to SDBS is 5:2, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0019] Take 3g of SGS and put it into 10g of DMAc, stir until it is completely dispersed (such as Figure 3 ), and then concentrated to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be tested by OM and SEM. Figure 4 b is the OM diagram, from which it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 b is a SEM image, and it can be seen that GO is present as a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in the form of a single piece. The above dispersion is spread on a membrane and dried to obtain a regenerated GO membrane, such as Figure 7 .
[0020] Example 3 A method for storing graphene oxide in a solid state, wherein SDBS is added to a 10 mg / g GO aqueous dispersion so that the mass ratio of GO to SDBS is 1:1, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0021] Take 3g of SGS and put it into 10g of THF, stir until it is completely dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Figure 4 c is the OM diagram, which shows that there is no obvious agglomeration or insoluble matter; Figure 5 Figure c is a SEM image, which shows that GO is present as a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in a single piece. The above dispersion is spread as a film and dried to obtain a regenerated GO film.
[0022] Example 4 A method for storing graphene oxide in a solid state, wherein SDBS is added to a 1 mg / g GO aqueous dispersion so that the mass ratio of GO to SDBS is 5:2, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0023] Take 3g of SGS and put it into 10g of 1,4-dioxane, stir until it is completely dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Figure 4d is the OM diagram, and it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 d is a SEM image, and it can be seen that GO is present as a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in a single piece. The above dispersion is spread as a film and dried to obtain a regenerated GO film.
[0024] Example 5 A method for storing graphene oxide in a solid state, wherein SDBS is added to a 20 mg / g GO aqueous dispersion so that the mass ratio of GO to SDBS is 5:2, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0025] Take 1g of SGS and put it into 10g of water, stir until it is completely dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Figure 4 e is the OM diagram, and it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 Figure e is a SEM image, and it can be seen that GO is present as a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in a single piece. The above dispersion is spread as a film and dried to obtain a regenerated GO film.
[0026] Example 6 A method for storing graphene oxide in a solid state, wherein SDS is added to a 10 mg / g GO aqueous dispersion so that the mass ratio of GO to SDS is 5:2, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0027] Take 5g of SGS and put it into 10g of water, stir until it is completely dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Figure 4 f is the OM diagram, and it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 Figure f is a SEM image, and it can be seen that GO is present as a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in a single piece. The above dispersion is spread as a membrane and dried to obtain a regenerated GO membrane.
[0028] Example 7 A method for storing graphene oxide in a solid state, wherein SA is added to a 10 mg / g GO aqueous dispersion so that the mass ratio of GO to SA is 5:2, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0029] Take 10g of SGS and put it into 10g of NMP, stir until it is completely dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Figure 4 g is the OM diagram, and it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 Figure g is a SEM image, and it can be seen that GO is present as a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in a single piece. The above dispersion is spread as a membrane and dried to obtain a regenerated GO membrane.
[0030] Example 8 A method for storing graphene oxide in the solid state, wherein PSS is added to a 10 mg / g GO aqueous dispersion so that the mass ratio of GO to SA is 5:2, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2 , no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0031] Take 2 g of SGS and put it into 10 g of DMF, stir until it is completely dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Figure 4 h is the OM diagram, and it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 h is a SEM image, and it can be seen that GO is a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in a single piece. The above dispersion is spread on the membrane and dried to obtain a regenerated GO membrane.
[0032] Example 9 A method for storing graphene oxide in a solid state, wherein SDBS is added to a 10 mg / g GO aqueous dispersion so that the mass ratio of GO to SDBS is 5:2, the mixture is stirred until the two are evenly mixed, and then dried at 40°C for 3 hours to obtain SGS. Figure 1 The obtained SGS was used for XRD test, and the results are as follows Figure 2, no π-π stacking seals appear, indicating that there is no physical cross-linking inside the SGS.
[0033] Take 2 g of SGS and put it into 10 g of a 1:1:1 mixed solution of DMF, DMAc and NMP, stir until completely dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14,000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Figure 4 i is the OM diagram, and it can be seen that there is no obvious agglomeration or insoluble matter; Figure 5 The i is a SEM image, and it can be seen that GO is present as a single piece in the dispersion. This shows that the obtained dispersion is uniform and GO exists in the form of a single piece. The above dispersion is spread on the membrane and dried to obtain a regenerated GO membrane.
[0034] Comparative Example 1 Take 1 g of GO powder prepared according to patent CN106966383A (purchased from Gaoxin Technology) and put it into 10 g of water and stir until dispersed. After standing for 1 h, obvious stratification phenomenon (such as Fig. 9 ).
[0035] The above dispersion was subjected to OM and SEM tests. Fig.10 a is the OM diagram, which shows the presence of obvious agglomeration or insoluble matter; Fig.11 Figure a is a SEM image, from which it can be seen that GO agglomerates in the dispersion. This shows that the GO powder used is difficult to disperse evenly in water.
[0036] Comparative Example 2 SDBS was added to 10 mg / g GO aqueous dispersion to make the mass ratio of GO to SDBS be 5:1, stirred until the two were evenly mixed, and dried at 40°C for 3 h to obtain SGS.
[0037] Take 1 g of SGS and put it into 10 g of water, stir until dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Fig.10 b is the OM diagram, which shows the presence of obvious agglomeration or insoluble matter; Fig.11 Figure b is a SEM image, from which it can be seen that GO agglomerates in the dispersion. This shows that the GO powder used is difficult to disperse evenly in water.
[0038] Comparative Example 3 SDBS was added to 10 mg / g GO aqueous dispersion to make the mass ratio of GO to SDBS be 5:2, stirred until the two were evenly mixed, and dried at 60°C for 3 h to obtain SGS.
[0039] Take 5 g of SGS and put it into 10 g of water, stir until dispersed, and then concentrate it to about 10 mg / g by centrifugation at 14000 rpm for 3 hours to obtain a dispersion, which can be used for OM and SEM testing. Fig.10 c is the OM diagram, which shows the presence of obvious agglomeration or insoluble matter; Fig.11 Figure c is a SEM image, which shows that GO agglomerates in the dispersion. This shows that the GO powder used is difficult to disperse evenly in water.
[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for solid-state storage of graphene oxide, characterized in that: Anionic surfactants or anionic polyelectrolytes are added to the graphene oxide aqueous solution and mixed evenly, and then the mixed solution is dried to prepare soluble graphene oxide solid (SGS).
2. The method according to claim 1, characterized in that The concentration of the graphene oxide aqueous solution is 1-20 mg / g.
3. The method according to claim 1, characterized in that The anionic surfactant is one of sodium dodecyl sulfonate (SDS), sodium dodecylbenzene sulfonate (SDBS), sodium stearate, sodium oleate, and sodium hexadecyl sulfate.
4. The method according to claim 1, characterized in that The anionic polyelectrolyte is one of sodium polystyrene sulfonate (PSS), sodium alginate (SA), sodium lauryl polyether sulfate (SLES), sodium polyacrylate, and polyvinyl ammonium phosphate.
5. The method according to claim 1, characterized in that The mass ratio of the graphene oxide aqueous solution to the ionic surfactant or the anionic polyelectrolyte is 10:3~1:
1.
6. The method according to claim 1, characterized in that The drying temperature of the drying treatment is 20°C to 40°C, and the drying time is three hours to one day.
Citation Information
Patent Citations
Method for preparing graphene powder
CN101993065A
Paper-like graphene microspheres and preparation method thereof
CN106966383A
Preparation method of easy-dispersible graphene powder and graphene powder prepared by method
CN105967179A
Preparation method and application of anionic polyelectrolyte modified graphene oxide
CN111635743A
Instant graphene oxide powder and preparation method thereof
CN112573515A